2014
DOI: 10.1508/cytologia.79.289
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Heteromorphic NORs and Chromosome Analysis of Rolland's Demoiselle, <i>Chrysiptera rollandi</i> (Perciformes, Pomacentrinae) by Conventional and Ag-NOR Staining Techniques

Abstract: Summary This is the first heteromorphic nucleolar organizer regions (NORs) and chromosome analysis of Rolland s demoiselle (Chrysiptera rollandi). Kidney cell samples were taken from five male and five female fish. Mitotic chromosome preparations were prepared directly from kidney cells. Conventional and Ag-NOR staining techniques were applied to stain the chromosomes. The results showed that the diploid chromosome number of C. rollandi was 2n=46, and the fundamental number (NF) was 50 in both males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This pattern suggests simple translocation in the karyotypic evolution of this group. Despite the importance of heteromorphic NORs, this does not appear to be the main evolutionary tendency in the karyotype of this subfamily, but may be characteristic of species groups (Kasiroek et al 2014). The chromosome of mitotic metaphase cells and the karyotypes of D. trimaculatus by conventional staining and Ag-NOR staining techniques are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern suggests simple translocation in the karyotypic evolution of this group. Despite the importance of heteromorphic NORs, this does not appear to be the main evolutionary tendency in the karyotype of this subfamily, but may be characteristic of species groups (Kasiroek et al 2014). The chromosome of mitotic metaphase cells and the karyotypes of D. trimaculatus by conventional staining and Ag-NOR staining techniques are shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Kashiwagi et al (2005) suggested that NOR-bearing chromosomes showed size variation among the species, but no intraspecific variation, and these chromosomes have been differentiated involving heterochromatin amplifications or translocation of NORs in the genus Dascyllus. However, some representatives of the subfamilies Pomacentrinae and Chrominae show marked heteromorphic NORs (two NORs from non-homologous chromosomes), such as Microspathodon chrysurus, Chrysiptera rollandi (Kasiroek et al 2014), Chromis insolata and C. flavicauda (Molina and Galetti 2002). This pattern suggests simple translocation in the karyotypic evolution of this group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetical and karyotypic studies have revealed variations of chromosomes in size, morphology, and number in various clades of plant and animal species (Al-Dakan and Al-Saleh 2015, Al-Qahtani et al 2014, Arslan and Zima 2014, Bagane et al 2014, Çakmak and Koca 2014, Deshpande et al 2014, El-Esawi and Sammour 2014, Gholave et al 2014, Haroun and Alotaibi 2015, Jantarat et al 2014a, Kaewmad et al 2014, 2014c, Kantek et al 2015, Kasiroek et al 2014, Kaur and Singhal 2015, Khakhong et al 2014, Kumar et al 2015, Kumar et al 2014, Li et al 2015, Martin et al 2015, Miura and Iwatsubo 2014, Parai and Mukherjee 2014, Park 2015, Patawang et al 2014a, Phimphan et al 2015, Pierozzi and Baroni 2014, Pinthong et al 2014, Qumsiyeh et al 2014, Rezaei et al 2014, Samanta et al 2015, Sato et al 2015, Tahami et al 2014, Venkatesh and Munirajappa 2015, Venkatesh et al 2014, Walia et al 2015. Cytogenetical techniques including banding methods and FISH have revealed the evolutionary process in structural and number changes of chromosomes (Lombello and Pinto-maglio 2014…”
mentioning
confidence: 99%